The silent mannequin disciplined, commodified, silenced bodies in Madelaine Chapsal’s Les Chiffons du Rêve - Diajeng Naomi Mercy Van Mary; Wening Udasmoro (Universitas Muhammadiyah Purwokerto, 2026)
The French haute couture industry has a long, deeply rooted history of systematically controlling women’s bodies through the aesthetics of the beauty process. This study examines how representations of the female body are presented as disciplined and commercialized objects in a collection of short stories written by Madeleine Chapsal in Les Chiffons du rêve, situating them within the socio-political context of the French fashion industry. Drawing on Wendy Harcourt’s theory of the politics of the body and Michel Foucault’s concept of “docile bodies”, the author has selected five short stories for analysis using close reading techniques. This study will identify three mechanisms or perspectives referring to Harcourt regarding interconnected forms of power: institutional subordination, commodification within luxury capitalism, and the internalization of aesthetic norms which over time slowly but surely influence the transformation of many women into individuals who ultimately discipline themselves. This study posits that the cold narrative style presented by Chapsal, the depiction of women’s bodies and “broken” models, alongside the abundant symbolism employed, serves as a function of critique and resistance against the historically entrenched patriarchal system that has been implemented and normalized within the world of haute couture from the outset, particularly regarding women and models. A key highlight that emerges is this: although a critique of oppression is presented, the narrative, as written and portrayed, simultaneously reproduces and normalizes the process of bodily compliance among women and models in every single chapter throughout the entire collection.